The effects of gamma irradiation on non-isothermal crystallization kinetics and microhardness of the Li2O-Al2O3-SiO2 glass-ceramic - Kaygili, Omer; Yavuz, Hulusi (Springer, 2010)
The effects of gamma irradiation on crystallization kinetics and microhardness properties of the Li(2)O-Al(2)O(3)-SiO(2) (LAS) glass-ceramic sample have been investigated. The glass-ceramic was irradiated to gamma-source (60)Co of 0.7 MGy. The crystallization kinetics of the irradiated and non-irradiated samples were characterized using differential scanning calorimetry. The crystallization kinetics and microhardness properties of the glass-ceramic changed the gamma irradiation, and the high dose of gamma irradiation affects significantly the crystallization kinetics and microhardness properties of the Li(2)O-Al(2)O(3)-SiO(2) glass-ceramic sample.
Keywords: Glass-ceramics; Crystallization kinetics; gamma-Irradiation effects; Microhardness